As correlações clínico-topográficas das afasias - Madalozzo, Danielle (2007)
Aphasia is a disorder that affects the language in its receptive and expressive, syntactic, semantic and morphologic aspects. The most common cause is the cerebrovascular accident (CVA). The authors of studies about the clinical-topographical correlations of the aphasias have been presenting variable results regarding the cerebral location of the language. The objective of this study was to establish the clinicaltopographical correlations of the fluent and non-fluent aphasias, observing the contributions of Spect scanning to map the affectec areas in the aphasias. A total of 29 patients with aphasia due to first episode of CVA comprised the study. They were submitted to language evaluation by means of selected proofs of the Boston Diagnosis Aphasias Examination (BDAE). Spect scanning was used to evaluate perfusion alterations in the whole encephalon , and it was analyzed by a nuclear doctor and a radiologist, in order to supply fidelity to the location data. After clinical evaluation, it was observed that 62% of the patients presented non-fluent aphasia and 38% fluent aphasia. It was not possible to classify 17% of the sample according to the classic types of aphasia. The analysis of the main components based on covariances allowed to relate the non-fluent aphasias mainly to the left and right frontal regions , left temporal region, presence of contralateral cerebelar diasquise to the left, subcortical regions , among others. The fluent aphasias are related to the inferior and superior left parietal regions . These data have corroborated for the concept of neural net in which several cortical , subcortical and cerebelar regions are involved to perform a linguistic task. In this way, this study showed that other cerebral regions participate in the language process as a neural circuit. Cerebral Spect provided different xi contributions from other image methods, adding important information on the participation of subcortical and cerebelar areas in the language process.